Anti‐CD40 antibody‐mediated costimulation blockade promotes long‐term survival of deep‐lamellar porcine corneal grafts in non‐human primates. (10th April 2017) - Kim, Jaeyoung; Kim, Dong Hyun; Choi, Hyuk Jin; Lee, Hyun Ju; Kang, Hee Jung; Park, Chung‐Gyu; Hwang, Eung‐Soo; Kim, Mee Kum; Wee, Won Ryang
Abstract: Background: Corneal xenotransplantation is an effective solution for the shortage of human donor corneas, and the porcine cornea may be a suitable candidate for the donor cornea because of its optical similarity with humans. However, it is necessary to administer additional immunosuppressants to overcome antigenic differences. We aimed to investigate the feasibility of porcine corneas with anti‐CD40 antibody‐mediated costimulation blockade in a clinically applicable pig‐to‐non‐human primate corneal xenotransplantation model. Methods: Five Chinese rhesus macaques underwent deep‐lamellar corneal transplantation using clinically acceptable sized (7.5 mm diameter) porcine corneal grafts. The anti‐CD40 antibody was intravenously administered on a programmed schedule. Graft survival, central corneal thickness, and intraocular pressure were evaluated. Changes in effector and memory T and B cell subsets and anti‐αGal and donor‐specific antibodies were investigated in the blood, and the changes in complement levels in the aqueous humor and blood were evaluated. Memory cell profiles in the anti‐CD40 antibody‐treated group were compared with those from the anti‐CD154 antibody‐treated group or rejected controls presented in our previous report. The changes in anti‐αGal, non‐αGal, and donor‐specific antibodies after 6 months were compared with baseline values. Results: Anti‐CD40 antibody‐mediated costimulation blockade resulted in the successful survival of xenocorneal grafts (>389, >382, >236, >201, and >61 days), with 80% reaching 6 months of survival. Injection of anti‐CD40 antibody considerably reduced the infiltration of inflammatory cells into the grafts and significantly blocked the complement response in the aqueous humor ( P =.0159, Mann‐Whitney U test). Systemic expansion of central or effector memory T cells was abrogated in the anti‐CD40 antibody‐treated primates compared with those in the rejected controls ( P <.05, Mann‐Whitney U test) or those in the anti‐CD154 antibody‐treated primates ( P >.05, Mann‐Whitney U test). The levels of anti‐αGal, non‐αGal, and donor‐specific antibodies at 6 months were not significantly increased compared with baseline levels ( P >.05, Wilcoxon signed rank test). Conclusions: An anti‐CD40 antibody‐mediated blockade appears to be effective immunosuppressive approach for porcine corneal deep‐lamellar xenotransplantation in primates.